Estimation of a Longitudinal Model to Decompose the Effects of an Advertising Stimulus on Family Consumption - Winer, Russell S. (Management Science, 1980)
A model which separates the various effects of an advertising experiment on a family's consumption behavior is estimated using consumer panel data. It is determined that there were significant transitory or short-run effects of the advertising, while permanent influences and price-advertising interactions were negligible. Implications of both the empirical results for management and the modeling approach for market researchers are discussed.